The Role of The Defendant in Improving The Performance of Lurah in West Binjai District, Binjai City - Nugroho, M. Gusty; Sihombing, Marlon; Adam, Adam (PERSPEKTIF, 2024)
This research aims to determine the role of the sub-district head in improving the performance of village heads in the West Binjai sub-district area and to determine the factors inhibiting the sub-district head in improving the performance of village heads in the West Binjai sub-district area. The results of the research show that the role of the sub-district head in improving the performance of sub-district government officials in the West Binjai area is categorized as good with general implementation including active, participative, and passive roles. The obstacles to improving the performance of village heads are that the quality of resources is still low because most village officials are limited to high school, and junior high school and some have even finished elementary school; village government organizations' regulatory policies are not yet perfect; the arranging limit at the town head level is low; furthermore, the offices and framework supporting functional government organization are still extremely poor. restricted, aside from upsetting the productivity and adequacy of work execution, it additionally can lessen the inspiration of carrying out officials, in this way eventually obstructing the accomplishment of objectives, undertakings, and work.